Morphometric Assessment and Tectonic Stress Orientation of Mount Dempo, South Sumatra, Indonesia - Bimantara Panca Utama; Refrizon; Arif Ismul Hadi; Nanang Sugianto; Dadin Mars Abimayu; Naela Sahada Salsabila; Adrian Daniel (Jurnal Geosains dan Remote Sensing, 2026)
Mount Dempo in South Sumatra lies within the Bukit Barisan volcanic arc, where interactions between volcanism and the Sumatra Fault Zone remain poorly understood. This study presents the first systematic morphometric assessment to determine the maximum horizontal stress (σHmax) orientation at Mount Dempo using high-resolution DEMNAS data and GIS-based analysis. Crater elongation, breach azimuth, and parasitic cone alignments from monogenetic features were measured—each azimuth recorded three times per feature to ensure precision. Statistical evaluation using the circular mean and Rayleigh test reveals a dominant σHmax orientation of 138° ± 12° (SE–NW), consistent with the oblique convergence between the Indo-Australian and Eurasian plates. These findings provide new quantitative constraints on stress-controlled magma migration pathways and contribute to the World Stress Map database for volcanic regions in Southeast Asia. The results also support improved volcanic hazard assessment frameworks in tectonically complex terrains.